Training Level Does Not Affect Auditory Perception of The Magnitude of Ball Spain in Table Tennis - Santos, Daniel P. R.; Barbosa, Roberto N.; Vieira, Luiz H. P.; Santiago, Paulo R. P.; Zagatto, Alessandro M. [UNESP]; Gomes, Matheus M. (De Gruyter Open Ltd, 2017)
Identifying the trajectory and spin of the ball with speed and accuracy is critical for good performance in table tennis. The aim of this study was to analyze the ability of table tennis players presenting different levels of training/experience to identify the magnitude of the ball spin from the sound produced when the racket hit the ball. Four types of forehand contact sounds were collected in the laboratory, defined as: Fast Spin (spinning ball forward at 140 r/s); Medium Spin (105 r/s); Slow Spin (84 r/s); and Flat Hit (less than 60 r/s). Thirty-four table tennis players of both sexes (24 men and 10 women) aged 18-40 years listened to the sounds and tried to identify the magnitude of the ball spin. The results revealed that in 50.9% of the cases the table tennis players were able to identify the ball spin and the observed number of correct answers (10.2) was significantly higher (X2 = 270.4, p <0.05) than the number of correct answers that could occur by chance. On the other hand, the results did not show any relationship between the level of training/experience and auditory perception of the ball spin. This indicates that auditory information contributes to identification of the magnitude of the ball spin, however, it also reveals that, in table tennis, the level of training does not interfere with the auditory perception of the ball spin.
Keywords: table tennis; ball rotation; auditory information; experience level